Comparative analysis of production and marketing aspects of deficit and surplus paddy production areas in Bangladesh - Ahmed, Junayed Uddin; Sultana, Maya (Research in Agriculture Livestock and Fisheries, 2024)
The study aimed to compare production and marketing aspects in deficit and surplus paddy production areas in Bangladesh. For this study, a face-to-face interview was conducted with a semi-structured questionnaire. The survey was carried out in two districts from February to March 2022. Data were collected from a total of 113 paddy farmers from Brahmanbaria, a deficit district, and 128 farmers from Habiganj, a surplus district. According to this study, farmers in surplus districts have excellent geographic characteristics such as medium-high land and a triple crop area, while farmers in deficit districts suffer unfavorable conditions such as low land and flooding. The study also discovered that there are differences between the districts in terms of land availability, paddy cultivation area, and cropping intensity. In production aspects, the size of the farmland and the productivity differ significantly at the 1% level between the districts. Deficit farmers produce less paddy per acre compared to farmers with surplus districts. In the paddy marketing channel, local paddy assemblers (LPA) are the dominant actors in the deficit and LPB/local paddy brokers in the surplus area. Farmers in surplus areas have more marketing facilities and get higher paddy revenue and profits compared to deficit districts. However, farmers in both districts are mostly dependent on traders to sell their produce. In that case, paddy marketing facilities can accumulate through farmers’ community investment and the organization of cooperative societies. It will help improve farmers’ negotiation power at the village level in both districts. Res. Agric. Livest. Fish. Vol. 11, No. 2, August 2024: 173-183